2023
DOI: 10.1111/gcb.16859
|View full text |Cite
|
Sign up to set email alerts
|

Human‐induced salinity changes impact marine organisms and ecosystems

Till Röthig,
Stacey M. Trevathan‐Tackett,
Christian R. Voolstra
et al.

Abstract: Climate change is fundamentally altering marine and coastal ecosystems on a global scale. While the effects of ocean warming and acidification on ecology and ecosystem functions and services are being comprehensively researched, less attention is directed toward understanding the impacts of human-driven ocean salinity changes.The global water cycle operates through water fluxes expressed as precipitation, evaporation, and freshwater runoff from land. Changes to these in turn modulate ocean salinity and shape t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 191 publications
0
5
0
Order By: Relevance
“…Nevertheless, other factors than those included in the study could have played a role in these changes. For example, salinity changes due to climate warming may impact planktonic organisms (e.g., through changes in respiration, disruption of cellular processes) and their habitats (e.g., changes in water column stratification) 136 . However, an analysis of a salinity dataset acquired at the study site, as shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other factors than those included in the study could have played a role in these changes. For example, salinity changes due to climate warming may impact planktonic organisms (e.g., through changes in respiration, disruption of cellular processes) and their habitats (e.g., changes in water column stratification) 136 . However, an analysis of a salinity dataset acquired at the study site, as shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this imbalance has been found to be amplified by human activities (Omerspahic et al, 2022; Röthig et al, 2023). For instance, brine discharge during seawater desalination can lead to an abnormal increase in salinity of the receiving water body in coastal marine environment, while the enhanced urban drainage may freshen nearshore seawater (Omerspahic et al, 2022; Röthig et al, 2023). Salinity fluctuations in seawater would alter the dissolved oxygen level, nutrient concentration, and stratification of the oceans, thereby posting an adverse impact on the respiration, metabolism, reproduction, and even disease immunity of marine organisms (Lehtonen et al, 2016; Guo et al, 2020; Galkanda-Arachchige et al, 2021; Lu et al, 2022; Lacy et al, 2023; Röthig et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Till 2017, the mean salinity contrast between the low and high salinity regions had increased by more than 5% (Cheng et al, 2020). Furthermore, this imbalance has been found to be amplified by human activities (Omerspahic et al, 2022; Röthig et al, 2023). For instance, brine discharge during seawater desalination can lead to an abnormal increase in salinity of the receiving water body in coastal marine environment, while the enhanced urban drainage may freshen nearshore seawater (Omerspahic et al, 2022; Röthig et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations